I’m coming to GEF you: Regulation of RhoGEFs during cell migration - Goicoechea, Silvia M (Cell Adh Migr, 2014)
Cell migration is a highly regulated multistep process that requires the coordinated regulation of cell adhesion, protrusion, and contraction. These processes require numerous protein–protein interactions and the activation of specific signaling pathways. The Rho family of GTPases plays a key role in virtually every aspect of the cell migration cycle. The activation of Rho GTPases is mediated by a large and diverse family of proteins; the guanine nucleotide exchange factors (RhoGEFs). GEFs work immediately upstream of Rho proteins to provide a direct link between Rho activation and cell–surface receptors for various cytokines, growth factors, adhesion molecules, and G protein-coupled receptors. The regulated targeting and activation of RhoGEFs is essential to coordinate the migratory process. In this review, we summarize the recent advances in our understanding of the role of RhoGEFs in the regulation of cell migration.